EM‐SON: efficient multimedia service over self‐organising Wi‐Fi network. Issue 4 (1st July 2018) - Singhal, Chetna; De, Swades
Abstract : This study presents eM‐SON, an adaptive framework for providing efficient multimedia services over self‐organising, hybrid Wi‐Fi networks. In this reconfigurable architecture, multimedia services can be received via a Wi‐Fi router, Wi‐Fi hotspot, or Wi‐Fi direct (i.e. device‐to‐device) mode. Experimental studies are performed to obtain user equipment (UE) battery discharge and QoS/QoE parameters for adaptive multimedia service (transmission, reception, and playback) over each of these Wi‐Fi configurations. These experiments are conducted on different types of UEs (smartphone, tablets) with multimedia content encoded at several quality and scalability levels, and transmitted on each of the Wi‐Fi configurations over varying load conditions and dynamic channel allocation. A centrally controlled framework is developed to optimise the multimedia content (adaptive transcoding) and network resource allocation (dynamic Wi‐Fi configurations and channel allocation) based on the dynamic UE and network resource constraints. The proposed solution combinedly improves the QoS (throughput, number of retransmissions, and delay), QoE, and energy‐efficiency performance of the UEs, while effectively serving an increased number of users in the system.